PENGARUH DESAIN RUANG RAWAT INAP TERHADAP PENGALAMAN PENYEMBUHAN PASIEN: STUDI PENDEKATAN EVIDENCE-BASED DESIGN DI RUMAH SAKIT SANTA MARIA PEKANBARU - Marison, Artian Ferry; Tela, I Nengah; Wongso, Jonny (SIGMA TEKNIKA, 2025)
The design of inpatient rooms plays a crucial role in enhancing patient comfort and supporting the healing process. Although Indonesia's healthcare regulations have promoted standardized inpatient care through the National Health Insurance (JKN) scheme, the implementation of design elements that consider patients’ psychological and physiological needs remains suboptimal. This study aims to examine the influence of inpatient room design on patient experience and recovery outcomes by applying the Evidence-Based Design (EBD) framework and Ulrich’s Supportive Design Theory, which emphasizes three core aspects: perceived control, social support, and positive distraction. The research was conducted at Santa Maria Hospital in Pekanbaru using a mixed-methods approach, combining quantitative data from Likert-scale surveys and qualitative data from interviews analyzed thematically. Findings reveal that physical elements of the inpatient room—such as natural lighting, environmental control, and indoor air quality—significantly affect patient satisfaction and healing outcomes. Moreover, noticeable differences were identified among class III patients based on room orientation and access to daylight. This study contributes to the development of more adaptive and human-centered healthcare design and supports the implementation of national policies on standardized inpatient services.